2001
DOI: 10.1023/a:1010704715979
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Plasma membranes isolated from pig liver contained almost no acid sphingomyelinase but significant neutral magnesium-dependent sphingomyelinase that was activated by phosphatidylserine. We report here the purification to apparent homogeneity of neutral sphingomyelinase of about 87 kDa from liver plasma membranes. The purified enzyme strictly required magnesium and had a neutral optimal pH. In contrast with neutral sphingomyelinase purified from other sources (such as brain), the enzyme purified from from liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A previous report suggested that an isolated compound, scyphostatin, has a structural resemblance to ceramide and may inhibit N-sphingomyelinase [ 88 ]. Moreover, some other N-sphingomyelinase inhibitor analogs have been developed, namely spiroexpoxide, [ 89 ] manumycin A, [ 90 ] alutenusin, [ 91 ] and ubiquinol [ 92 ].…”
Section: Therapeutics Targeting Ceramide Biosynthesismentioning
confidence: 99%
“…A previous report suggested that an isolated compound, scyphostatin, has a structural resemblance to ceramide and may inhibit N-sphingomyelinase [ 88 ]. Moreover, some other N-sphingomyelinase inhibitor analogs have been developed, namely spiroexpoxide, [ 89 ] manumycin A, [ 90 ] alutenusin, [ 91 ] and ubiquinol [ 92 ].…”
Section: Therapeutics Targeting Ceramide Biosynthesismentioning
confidence: 99%
“…These results suggest that caveolar nSMase may be involved in TNF‐α signalling. Working on a different system, namely pig liver plasma membranes, Martin et al [54] isolated a Mg 2+ ‐dependent nSMase that was not inhibited by glutathione but was inhibited by ubiquinol and other lipophilic antioxidants. Also relevant in this context is the somewhat forgotten report of a latent nSMase in chicken erythrocyte membranes [55].…”
Section: Sphingomyelinasesmentioning
confidence: 99%
“…108 Another hydroquinone-based compound, ubiquinol (72) (CoQ 10 H 2 , Figure 23), was reported to inhibit Mg 2+ -dependent nSMase of pig liver plasma membranes (>90% inhibition at 100 μM following 15 min preincubation) in a noncompetitive manner with respect to sphingomyelin. 109 Subsequent studies releveled that inhibition by ubiquinol ( 72) is time-dependent, displaying a greater degree of potency when preincubated for 60 min. 110 Furthermore, CoQ 6 H 2 (73) (Figure 23) was found to have the optimal isoprenoid side chain length for nSMase inhibition among several homologs.…”
Section: Sphingomyelinasementioning
confidence: 99%
“…Compound 71 (Figure ), the corresponding quinolone derivative of 69 , was also found to potently inhibit nSMase of rat brain microsomes with a IC 50 value of 0.8 μg/mL (4.2 μM) . Another hydroquinone-based compound, ubiquinol ( 72 ) (CoQ 10 H 2 , Figure ), was reported to inhibit Mg 2+ -dependent nSMase of pig liver plasma membranes (>90% inhibition at 100 μM following 15 min preincubation) in a noncompetitive manner with respect to sphingomyelin . Subsequent studies releveled that inhibition by ubiquinol ( 72 ) is time-dependent, displaying a greater degree of potency when preincubated for 60 min .…”
Section: Sphingomyelinasementioning
confidence: 99%